2014
DOI: 10.1177/1470320313512389
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin IV and the human esophageal mucosa: An exploratory study in healthy subjects and gastroesophageal reflux disease patients

Abstract: The AT4R and formation enzymes of AngIII and AngIV are present in the human esophageal epithelium. Moreover, the present results suggest that AngIV exert regulatory impact on the epithelium and that RAS is involved in mucosal aberrations associated with GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…23 In a recent study we showed that the AP/AngIV/IRAP axis was expressed and functional in the human esophageal mucosa. 24 However, no data are available describing the effects of the AP/AngIV/IRAP axis in the human small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…23 In a recent study we showed that the AP/AngIV/IRAP axis was expressed and functional in the human esophageal mucosa. 24 However, no data are available describing the effects of the AP/AngIV/IRAP axis in the human small intestine.…”
Section: Introductionmentioning
confidence: 99%